To the 40-th anniversary of the Ukrainian INIS center - I. M. Vyshnevskyi; Zh. I. Pysanko; A. I. Lypska; O. M. Kuprava; L. M. Lamonova (Ядерна фізика та енергетика)
40th years experience of Ukrainian INIS Center is described. INIS Сenter is a structural unit of the Institute for Nuclear Research, National Academy of Sciences of Ukraine (Kyiv). The Center carries out the goals such as: the selection of information in the field of nuclear science and technology, processing of the selected publications on the requirements and regulations of IAEA, distribution of the information from the INIS database and non-conventional literature database, statistical and semantic analyses on certain problems. By the number of the annual input Ukrainian INIS center regularly ranks 12th among 128 countries and 24 international organizations.